2019
DOI: 10.1287/orsc.2018.1268
|View full text |Cite
|
Sign up to set email alerts
|

Blurred Lines: How the Collectivism Norm Operates Through Perceived Group Diversity to Boost or Harm Group Performance in Himalayan Mountain Climbing

Abstract: We develop and test a theory that reconciles contradictions regarding how collectivistic norms influence group performance. We draw on the perceived diversity literature to hypothesize that collectivistic norms cause group members to "blur" demographic differences, resulting in a shared perception that group members are more similar to one another than they actually are. Whether this benefits or harms group performance depends on the level of objective diversity in the group and the relevance of the perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 103 publications
2
23
0
Order By: Relevance
“…We assume that the leader is motivated to understand the team’s needs and manage team diversity (see also Nishii, Khattab, Shemla, & Paluch, 2018). Additionally, as diversity has greater potential to benefit performance on complex and interdependent rather than simple and independent tasks (Bowers et al, 2000; Chatman, Greer, Sherman, & Doerr, 2019; Jehn, Northcraft, & Neale, 1999; Van der Vegt & Janssen, 2003; Wegge, Roth, Neubach, Schmidt, & Kanfer, 2008), our analysis focuses on interdependent teams working on more complex tasks (e.g., problem-solving, creativity, decision-making). Finally, we examine leader effectiveness at the team level.…”
Section: Definitions and Scope Of The Current Modelmentioning
confidence: 99%
“…We assume that the leader is motivated to understand the team’s needs and manage team diversity (see also Nishii, Khattab, Shemla, & Paluch, 2018). Additionally, as diversity has greater potential to benefit performance on complex and interdependent rather than simple and independent tasks (Bowers et al, 2000; Chatman, Greer, Sherman, & Doerr, 2019; Jehn, Northcraft, & Neale, 1999; Van der Vegt & Janssen, 2003; Wegge, Roth, Neubach, Schmidt, & Kanfer, 2008), our analysis focuses on interdependent teams working on more complex tasks (e.g., problem-solving, creativity, decision-making). Finally, we examine leader effectiveness at the team level.…”
Section: Definitions and Scope Of The Current Modelmentioning
confidence: 99%
“…1 These norms are considered central to defining an organization’s culture. Collaboration, which is a basic dimension of organizing (e.g., Chatman, Greer, Sherman, & Doerr, 2019), increases employees’ productivity by emphasizing the importance of coordinating with relevant others to accomplish group and organizational goals and promotes feelings of connectedness at work (Edmondson, 1999). Norms of innovation and adaptability encourage measured risk-taking and experimentation with novel ideas and approaches—leading organizations to develop new products and services (Anderson, Potočnik, & Zhou, 2014; Chatman et al, 2014).…”
Section: Organizational Mindset and Cultural Normsmentioning
confidence: 99%
“…Rather than being driven by the team's individual attributes, rivalry perceptions varied at the dyad level and were the highest when teams were similar, had a history of repeated interactions, and competed in evenly matched competitions. These findings were novel as they revealed that the underlying psychological components of rivalry were subjective and relational, which contrasted with prior work that had generally used the word rivalry and competition as synonyms or defined a subset of competitors as rivals based either on more objective features (such as threats) or on current—rather than past—features or events (such as the exchange of competitive moves; Chen, 1996).…”
Section: Examples Of Management Research Using Sports Datamentioning
confidence: 59%
“…Sports also present positive examples of inclusivity, for example, by providing equal opportunities to people with disabilities (as in sailing, where in the International 2.4mR boat class, both able-bodied and disabled athletes participate on equal terms, and where a disabled athlete became a world champion), by representing a way to help migrants integrate (e.g., teams of migrants playing in local soccer leagues), and by affording children in less-developed countries access to education (e.g., the UNICEF-supported program in Nigeria helping children and adolescents-especially girls-to get an education via specific academies that combine academics and soccer, thus increasing their chances of professional success). Recent work leveraging sports data has started to deal with and identify biases, differences in treatment, and more in general exclusion-as well as inclusion-based on a variety of dimensions, such as race (Ertug & Maoret, 2020;Pope et al, 2018;Timmerman, 2007;Zhang, 2017Zhang, , 2019, gender (Adriaanse, 2016;Micelotta, Washington, & Docekalova, 2018;Ortlieb & Sieben, 2019), nationality (Chatman, Greer, Sherman, & Doerr, 2019), and core-periphery position (Christie & Barling, 2010;Fonti & Maoret, 2016;Humphrey, Morgeson, & Mannor, 2009;Stuart, 2017). Some work has also highlighted how sports can provide a more inclusive environment (e.g., better career prospects across genders; cf.…”
Section: Exploration Of Emerging Phenomenamentioning
confidence: 99%